1993
DOI: 10.1007/bf03345827
|View full text |Cite|
|
Sign up to set email alerts
|

Interference of thyroperoxidase on immuno-cytochemical determination of steroid receptors in thyroid tissue

Abstract: The presence of sexual steroid receptor proteins in thyroid tissue has been previously demonstrated by biochemical means. The aim of this study was to determine the estrogen (ER) and progesterone (PR) receptors in malignant (12 papillary and 1 follicular carcinoma) and nonmalignant (19 multinodular goiters, 1 Graves' disease, 1 Hashimoto's thyroiditis) thyroid diseases using immunocytochemical assay employing monoclonal anti-ER and anti-PR antibodies and the peroxidase-antiperoxidase technique. Positive result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The presence of estrogen receptors in the thyroid suggests a direct action of estrogens and estrogenic-stimulating drugs on the gland. [23][24][25] Also, some experiments using thyrocytes in vitro have demonstrated that estrogen has a definite role in the proliferation of these cells. 5,6,26,27 However, some studies have shown that the effects of estrogen and tamoxifen on thyroid gland may be rather indirect, as a consequence of increased serum levels of thyroxine-binding globulin (TBG) and the associated changes in thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of estrogen receptors in the thyroid suggests a direct action of estrogens and estrogenic-stimulating drugs on the gland. [23][24][25] Also, some experiments using thyrocytes in vitro have demonstrated that estrogen has a definite role in the proliferation of these cells. 5,6,26,27 However, some studies have shown that the effects of estrogen and tamoxifen on thyroid gland may be rather indirect, as a consequence of increased serum levels of thyroxine-binding globulin (TBG) and the associated changes in thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in TG suggests a reduced liberation of T4 during the secretory process of thyroid hormones, which could be the mechanism behind the reduction in plasma FT4 and FT3. Thyroid tissue is known to express the oestrogen receptor [15]. Because an increase in TG also is seen during pregnancy, the observed elevation of TG in plasma may represent an oestrogen-agonistic effect of tamoxifen [16].…”
Section: Discussionmentioning
confidence: 99%
“…These events can confound the specificity of immunoreactive signal and can lead to increased unspecific antibody binding (Larsson, 1988). The endogenously produced peroxidase, an important factor in pathogenesis of ischemic tissue damage (Bazan et al, 1995;Hall et al, 1993;Kinuta et al, 1989;Sakamoto et al, 1991) and part of the repair mechanisms after ischemia (Takizawa et al, 1994), confounds the correlation of enzyme activity to bound antibody using the immunoperoxidase method (Giani et al, 1993). Although methods to inactivate peroxidase are available (Larsson, 1988;Malorny et al, 1988), these approaches are not always used and if used, the effectiveness and completeness of the inactivation is not assessed routinely.…”
Section: Introductionmentioning
confidence: 98%